2018
DOI: 10.12659/msm.911853
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of User Interface for Ventilators Based on Respiratory Therapists’ Performance, Workload, and User Experience

Abstract: BackgroundPoor ergonomic design of ventilators can result in human errors. In this study, we evaluated the ergonomics of ventilators through respiratory therapists’ performance, workload, and user experience.Material/MethodsSixteen respiratory therapists were recruited to this usability study of 3 ventilators. Participants had to perform 7 tasks on each ventilator. Respiratory therapists’ performance was measured by task errors of all tasks for each participant. Workload was measured by objective measurement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Published studies have confirmed that a shorter blink duration and a lower blink rate indicate an increasing physiological workload. 15,23,35 Significant differences were also found for blink duration and blink rate between the two radiotherapy systems when cipants performed tasks with these systems. According to the results in Table 3, a longer blink duration (Varian: 0.14 6 0.02, Shinva: 0.12 6 0.03) and a higher blink rate (Varian: 0.45 6 0.37, Shinva: 0.25 6 0.21) were observed for participants with the Varian Trilogy, which means a lower physiological workload was observed for the Varian Trilogy.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Published studies have confirmed that a shorter blink duration and a lower blink rate indicate an increasing physiological workload. 15,23,35 Significant differences were also found for blink duration and blink rate between the two radiotherapy systems when cipants performed tasks with these systems. According to the results in Table 3, a longer blink duration (Varian: 0.14 6 0.02, Shinva: 0.12 6 0.03) and a higher blink rate (Varian: 0.45 6 0.37, Shinva: 0.25 6 0.21) were observed for participants with the Varian Trilogy, which means a lower physiological workload was observed for the Varian Trilogy.…”
Section: Discussionmentioning
confidence: 90%
“…24 Overall, blink rate and blink duration are inversely proportional to the degree of physiological workload. 15,23 Perceived workload. Perceived workload was evaluated based on the NASA Task Load Index (NASA-TLX) questionnaires.…”
Section: User Workloadmentioning
confidence: 99%
See 1 more Smart Citation
“…A user evaluation questionnaire was developed based on previous research [10,[12][13][14] to provide a standardised template for gathering the required formative feedback from end users. The questions were checked against the task scenario and professional practice by the clinical authors and adapted to align with the MHRA Specification [5].…”
Section: User Evaluation Questionnairementioning
confidence: 99%
“…The NASA-TLX has been used for assessing the usability of ventilators. 19,21,24 User experience A questionnaire assessing the ease to maintain (1 very difficult to 5 very easy), friendly to maintain (1 very bad to 5 very good) and willingness to use (1 certainly not to 5 certainly) was used to evaluate user experience of the participants. Higher scores indicate a better user experience.…”
Section: Perceived Workloadmentioning
confidence: 99%